Undang-Undang Informasi dan Transaksi Elektronik Bagi Perguruan Tinggi - Ria Safitri (Faculty of Sharia and Law UIN Syarif Hidayatullah Jakarta, 2018)
Abstract.Globalization of information has placed Indonesia as part of the world information society, thus requiring the establishment of regulations on information and electronic transactions at the national level as answers to developments that occur, both at regional and international levels.Based on these conditions, the Government of the Republic of Indonesia has enacted the Law of the Republic of Indonesia Number 11 of 2008 concerning Information and Electronic Transactions (hereinafter abbreviated as ITE Law) in the State Gazette of the Republic of Indonesia of 2008 Number 58.Information technology is very useful for university development strategies. Some forms of university development strategies that can utilize information technology and electronic transactions, namely the fields of education, research and development of science, development of the field of community service, development of human resources, development of fields of cooperation, development of university management, development of facilities and infrastructure and development source of funds.The provisions in the ITE Law (including the threat of sanctions) certainly constitute one side of normative efforts to protect the development of higher education institutions that have used information technology. In addition to the provisions of the prohibitions in the ITE Law, it also regulates matters that are prohibited but are considered not criminal acts, because one's actions are intended to conduct research activities, test Electronic Systems, to protect the Electronic System itself legally and not fight law. This provision encourages and protects lecturers / researchers from universities or research institutes of universities to conduct research for research institutions. Keywords: ITE Law, Electronic Transactions, Information Technology. Abstrak.Globalisasi informasi telah menempatkan Indonesia sebagai bagian masyarakat informasi dunia sehingga mengharuskan dibentuknya pengaturan tentang informasi dan transaksi elektronik di tingkat nasional sebagai jawaban perkembangan yang terjadi baik di tingkat regional maupun internasional. Berdasarkan kondisi tersebut maka Pemerintah Negara Republik Indonesia telah mengundangkan Undang-Undang Republik Indonesia Nomor 11 Tahun 2008 tentang Informasi dan Transaski Elektronik (selanjutnya disingkat UU ITE) dalam Lembaran Negara Republik Indonesia Tahun 2008 Nomor 58. Teknologi informasi sangat bermanfaat untuk strategi pengembangan perguruan tinggi. Beberapa wujud strategi pengembangan perguruan tinggi yang dapat memanfaatkan teknologi informasi dan transaksi elektronik yaitu bidang pendidikan, penelitian dan pengembangan ilmu, pengembangan bidang pengabdian kepada masyarakat, pengembangan sumber daya manusia, pengembangan bidang kerjasama, pengembangan manajemen perguruan tinggi, pengembangan bidang sarana dan prasarana dan pengembangan sumber dana. Ketentuan dalam UU ITE (termasuk ancaman sanksinya) tentu merupakan satu sisi upaya normatif untuk melindungi pengembangan perguruan tinggi yang telah memanfaatkan teknologi informasi. Di samping adanya ketentuan larangan-larangan tersebut dalam UU ITE juga mengatur hal-hal yang merupakan larangan tetapi dianggap bukan tindak pidana, karena perbuatan seseorang itu ditujukan untuk melakukan kegiatan penelitian, pengujian Sistem Elektronik, untuk perlindungan Sistem Elektronik itu sendiri secara sah dan tidak melawan hukum. Ketentuan ini mendorong dan melindungi para dosen/peneliti perguruan tinggi atau lembaga penelitian perguruan tinggi melakukan penelitian-penelitianbagi lembaga penelitian. Kata Kunci: Undang-Undang ITE, Transaksi Elektronik, Teknologi Informasi.